2010
DOI: 10.1080/00288233.2010.515937
|View full text |Cite
|
Sign up to set email alerts
|

Perennial pastures for recharge control in temperate drought-prone environments. Part 1: productivity, persistence and herbage quality of key species

Abstract: Perennial-based pasture swards potentially offer land managers the capacity for recharge control in temperate cropping zone environments to satisfy the dual role of fostering increased agricultural productivity and reduced deep drainage. This study evaluated the productivity, persistence and herbage quality of lucerne (Medicago sativa L.), phalaris (Phalaris aquatica L.), chicory (Cichorium intybus L.), perennial veldt grass (Ehrhata calcycina Sm.), grazing brome (Bromus stamineus E. Desv.), plantain (Plantago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 48 publications
1
31
0
1
Order By: Relevance
“…The botanical composition of grassland should include species that are able to withstand the changing conditions. Recent research has shown considerable differences in growth and digestibility among grass species under drought (Hayes et al, 2010). However, more research is necessary as to which species and genotypes are best suited for permanent grassland in Central Europe managed for high yielding dairy cows.…”
Section: Impacts On Quantity and Quality Of Fodder Productionmentioning
confidence: 99%
“…The botanical composition of grassland should include species that are able to withstand the changing conditions. Recent research has shown considerable differences in growth and digestibility among grass species under drought (Hayes et al, 2010). However, more research is necessary as to which species and genotypes are best suited for permanent grassland in Central Europe managed for high yielding dairy cows.…”
Section: Impacts On Quantity and Quality Of Fodder Productionmentioning
confidence: 99%
“…accounted for in the model -namely poor establishment (Li et al 2010) -have influenced the 621 production of the winter-active cultivar (SARDI 7). 622 623 An area of uncertainty concerns the growth, development and functioning of lucerne roots.…”
Section: Seasonal Growth Patterns and Differences Between Winter Actimentioning
confidence: 99%
“…This was done by placing a 1 m 2 quadrat (divided into squares of 0.1 m)0.1 m) over the sampling area and counting the percentage of squares occupied or partially occupied by the base of a sown perennial plant. Further details on basal frequency of the treatments are given by Hayes et al (2010).…”
Section: Plant Persistencementioning
confidence: 99%
“…A residual of 500Á800 kg/ha of above-ground biomass remained on the plots following defoliation. Further details on herbage yields of various treatments are described by Hayes et al (2010).…”
Section: Agronomic Managementmentioning
confidence: 99%
See 1 more Smart Citation